Water-soluble hyperbranched poly(phenyleneethynylene)s: Facile synthesis, characterization, and interactions with dsDNA. (24th February 2015) - Huang, Yan-Qin; Zhang, Rui; Song, Cai-Xia; Jiang, Rong-Cui; Liu, Xing-Fen; Zhang, Guang-Wei; Fan, Qu-Li; Wang, Lian-Hui; Huang, Wei
Abstract: Two novel water-soluble hyperbranched poly(p-phenyleneethynylene)s (HBP1′ and HBP2′) bearing different contents of oligo(ethylene oxide) (OEO) side chains with ammonium end groups were synthesized by the facile "A2 + B2 (or A2 ′) + C3 " protocol based on Sonogashira polymerization. Their linear analog (LP2′) was also synthesized for comparative investigation. The optical properties of the neutral precursory polymers in THF and final cationic conjugated polyelectrolytes (CCPs) in aqueous solution were studied. Compared with LP2′, HBP1′ exhibited increased water solubility and fluorescence quantum yield despite its lower charge density, and HBP2′, with the similar charge density as LP2′, showed the best water solubility and the highest fluorescence quantum yield among the three CCPs. This indicated that the introduction of hyperbranched structure into conjugated polyelectrolytes was an efficient way to improve water solubility and fluorescence quantum yield because intermolecular aggregation was remarkably prevented. The interactions among the three CCPs and double-stranded DNA (dsDNA) were studied using ethidium bromide (EB) as the fluorescent probe. The electrostatic bindings of the three CCPs with dsDNA/EB complex resulted in displacement of EB from dsDNA to the solution accompanied by the quenching of EB fluorescence. Both HBP1′ and HBP2′ bound to dsDNA more efficiently than LP2′, and HBP2′ formed the most stable complex with dsDNA, suggesting that dsDNA might enter the cavities of single-molecular globular architectures of these hyperbranched conjugated polyelectrolytes and induced additional host-guest spatial interactions. Hence, HBP1′ and HBP2′ may be proved very useful in gene delivery or DNA biosensor applications. Graphical abstract: Highlights: Water-soluble hyperbranched poly(phenyleneethynylene)s (PPEs) with different cationic charge densities were synthesized. Simple ''A2 + B2 (or A2 ′) + C3 '' protocol was used in the synthesis of hyperbranched PPEs. Hyperbranched structure helped to improve water solubility and fluorescence quantum yield of conjugated polyelectrolytes. The hyperbranched PPE with higher cationic charge density formed the most stable complex with double-stranded DNA (dsDNA). dsDNA might enter the cavities of hyperbranched structure to complex with the PPEs, leading to improved binding stability.